Systems Biology Integration and Screening of Reliable Prognostic Markers to Create Synergies in the Control of Lung Cancer Patients - Kaushik, Aman Chandra; Mehmood, Aamir; Wei, Dong-Qing; Dai, Xiaofeng (Frontiers in Molecular Biosciences, 2020)
This study aims to achieve a clearer and stronger understanding of all the mechanisms involved in the occurrence as well as in the progression of lung cancer along with discovering trustworthy prognostic markers. We combined four gene expression profiles (GSE19188, GSE19804, GSE101929, and GSE18842) from the GEO database and screened the commonly differentially expressed genes. We performed differential expressed groups analysis on commonly differentially expressed genes, alteration and mutational analysis and expression level verification of core differential genes were performed. Systems biology discoveries in our examination are predictable with past reports. Curiously, our examination revealed that screened biomarkers adjustments, for the most part, co-exist in lung cancer. After screening 952 commonly differentially expressed genes we found that the up-regulation of NMU and GTSE1 in the case of lung cancer is related to poor prognosis. On the other hand, FOS CDKN1C expression is associated with poor prognosis is responsible for the down-regulation of CDKN1C and FOS. Changes in these qualities are on free pathways to lung cancer and are not usually of combined quality variety. Even though biomarkers were related to both survival occasions in our examination, it gives us another point of view to all the while playing out the investigation of hereditary changes and clinical highlights employing information mining. Based on our results we found potential and prospective clinical applications in GTSE1, NMU, FOS, and CDKN1C to act as prognostic markers in case of lung cancer.